Indonesia’s Crude Palm Oil (CPO) Performance: Why Do Export Activities Exist? - Aini, Halia Butra; Usmayanti, Vivi; Sari, Dwi Darma Puspita (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the performance of Indonesia’s CPO exports and the effect of world CPO prices, rupiah exchange rate per US dollar and CPO production on the supply of CPO export in Indonesia from 1995-2020. The method that used in this research is Error Correction Model (ECM). The results of descriptive analysis are reflected: (a), the export volume of Indonesia’s CPO is very fluctuating in relation to the development of production variables, the value of the rupiah per US dollar and the world CPO export price; (b), the competitiveness of Indonesia’s CPO exports computed by the RCA Index reflects a relatively low competitiveness are less than one, but the trend has improved since 2012, where the RCA Index is greater than one. The regression results showed that, in the long-term, CPO production have a positive and significant impact on the CPO exports growth during the period, whereas in the short term the production have a negative and insignificant effect. The world price of CPO in the long and short-term prices have a negative and insignificant effect. The rupiah exchange rate per US dollars in the long term and short term have negative and significant effect. In the long term all independent variables have significant effect on the dependent variable, while in the short term all the variables have no significant effect on export volume variables.